Efeitos do treino de tronco e alcance em lactentes pré-termo: ensaio clínico randomizado controlado - Zambello, Vanessa (Universidade Federal de São Carlos, 2019)
Objective: To investigate the effects of a trunk and reaching training on the level of trunk control, on proximal and distal adjustments, and gross motor skills of moderate to late preterm infants at reaching onset. Methods: This is a single-blinded, randomized controlled trial. The participants were 16 moderate to late preterm infants (gestational age at birth 35.29 ± 1.09 weeks) who were allocated into two groups: experimental (trunk and reaching training) (17.29 ± 0.43 weeks of corrected age) or control (social training) (16.60 ± 1.53 weeks of corrected age). All infants were tested three times: 1) pre-test, performed 3 to 5 days after reaching onset and immediately before training; 2) post-test, performed immediately after 12 days of training; and 3) retention, performed seven days after post-test. The experimental protocol had a total duration of 19 days, and the exercises were performed during 12 consecutive days. All infants were evaluated by the Segmental Assessment of Trunk Control (SATCo) to identify the level of trunk control, assessment of proximal and distal reaching settings and by the Alberta Infant Motor Scale (AIMS) to measure gross motor function. During the trunk and reaching training protocol, six sessions were administered by a physical therapist and six were performed by the parents/guardians. The trunk and reaching training was composed of activities performed in reclined, supine, prone, sitting and standing postures over stable and unstable surfaces, with visual, tactile and auditory stimuli from several toys, and under random practice condition. The social training protocol was applied by parents / guardians who were trained to carry out the guidelines contained in a booklet. Infants in this group were positioned in the same postures as the experimental group, and received verbal and visual stimulation. The level of trunk control, frequency of reaches, proximal and distal adjustments, and AIMS scores were the primary outcomes. Grasping was the secondary outcome. Results: There were no differences between groups in any of the variables. There was an increase in open-hand reaches in the Time factor for the experimental group and control group in the post-test and in the retention when compared to the pre-test (p < 0.01), and in the retention when compared to the post-test (p < 0.01). It was observed in the control group, increase of reaches with the vertical hand in the Time factor in the retention when compared to the pre-test (p = 0.02). There was an increase of reaches with grasping in the Time factor in the experimental group in the retention when compared to the pre-test (p < 0.01) and in the control group in the post-test and retention when compared to the pre-test (p < 0.01). In the experimental group and control group there was increase in AIMS scores in the post-test and in the retention when compared to the pre-test (p < 0.01), and in the retention when compared to the post-test (p < 0.01). Conclusion: Our findings suggest that trunk and reaching training was not superior to social training. Effects on the level of trunk control, reaching behavior and gross motor function seem to require stimulation for longer periods of time.
Effects of training trunk control and reaching in preterm infants: a randomized controlled trial
Keywords: Prematuro; Alcance; Desenvolvimento infantil; Equilíbrio postural; Premature; Reaching; Child development; Postural balance; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL; CIENCIAS DA SAUDE